Support for sex education and teenage pregnancy prevention programmes in the USA: results from a national survey of likely voters - Kantor, Leslie; Levitz, Nicole; Holstrom, Amelia (Sex Education: Sexuality, Society and Learning, 2020)
Support for sex education in middle and high school and for the inclusion of a variety of topics in sex education programmes is strong among likely voters in the USA. This survey was conducted with a diverse sample of 965 adults who were invited from the largest probability-based panel in the USA. In addition to supporting sex education in schools, likely voters support continued government funding for teenage pregnancy prevention programmes and want those programmes to include abstinence as well as birth control and sexually transmitted disease (STD) prevention. There are some differences in support for the inclusion of particular topics in sex education among likely voters by political affiliation. Analyses adjusting for race/ethnicity, income, employment, education, age and gender, found that Republicans were more likely to support the inclusion of abstinence, while Democrats were more likely to support the inclusion of birth control, healthy relationships, consent and sexual orientation. There were no differences between Democrats and Republicans in support for including puberty and STDs, including HIV. This investigation adds to a growing literature showing that there is very high support for sex education and federal funding of teenage pregnancy prevention programmes in the USA.